2011
DOI: 10.1051/epjconf/20111502005
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Effects of Silver Ions on Ionic Conductivities of Molten Silver Halides

Abstract: Abstract. Ionic conductivities of molten (RbX) c (AgX) 1-c (X = Cl and I) mixtures were measured to clarify the concentration effects of silver ions on ionic conductivities of molten silver halides. It is found that the addition of RbX to molten AgX rapidly reduces the ionic conductivity with 0 ≤ c ≤ 0.4. It suggests that strong Ag-Ag correlation is necessary to fast conduction of Ag ions in molten state. The absolute values of ionic conductivity for (RbCl) c (AgCl) 1-c are larger than those for (RbI) c (AgI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…4 together with that for molten (AgI) 1-x (RbI) x reported in the earlier paper [9]. The E a for molten (AgI) 1-x (RbI) x rapidly increases in the range of 0.2 < x < 0.4, suggesting that a large energy is needed to move large and heavy Rb ions, and Rb ions would obstruct the Ag-conduction path in the high RbI-concentration [9]. On the other hand, the E a for molten (AgI) 1-x (CuI) x mixtures gradually increases with increasing CuIconcentration.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…4 together with that for molten (AgI) 1-x (RbI) x reported in the earlier paper [9]. The E a for molten (AgI) 1-x (RbI) x rapidly increases in the range of 0.2 < x < 0.4, suggesting that a large energy is needed to move large and heavy Rb ions, and Rb ions would obstruct the Ag-conduction path in the high RbI-concentration [9]. On the other hand, the E a for molten (AgI) 1-x (CuI) x mixtures gradually increases with increasing CuIconcentration.…”
supporting
confidence: 75%
“…In the present study, we report the ionic conductivities of molten CuI and molten (AgI) 1-inner diameter, and four carbon electrodes were inserted in small tapered holes of the cell [8,9]. The four carbon electrodes were fastened by nickel bands to prevent a leakage of the liquid sample at higher temperature.…”
mentioning
confidence: 99%
“…The diffusion coefficients D α (10 -5 cm 2 /s) (α = Na, Rb, I) and ionic conductivities σ calculated by the MD simulations for molten NaI, RbI and their mixture at 973 K are summarized in Table 2 with experimental literature values for pure NaI [12] and RbI [13]. Ionic conductivities of the MD simulations are estimated by using Nernst-Einstein equation…”
Section: " ! "mentioning
confidence: 99%
“…Although we used the rigid ion model in this study, if we consider a polarizable ion model, the cation diffusion would become large. However, polarization effects on NaI, RbI, and their mixture would be weak compared to silver (or cupper) halides [13][14][15][16][17][18][19][20] and zinc halides [21,22]. Ciccotti et al have reported that D Na and D I for pure NaI at 1081K are 9.4 × 10 -5 and 6.8 × 10 -5 cm 2 /s, respectively [3].…”
Section: " ! "mentioning
confidence: 99%